Hubungan Antara Beban Kerja Dengan Stres Kerja Pada Pegawai Di Badan Perencanaan, Penelitian, Dan Pengembangan (Bappelitbang) - Angel Pradita B Manalu; Junita Cahyaningtyas; Vemi Helita Malev Purba; Mukhaira El Akmal; Sri Hartini (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the relationship between workload and work stress among employees at the Planning, Development, Research, and Development Agency (Bappelitbang). The research is based on increasing job demands and task volume that may contribute to psychological pressure among employees. A quantitative correlational design was employed in this study. The sample consisted of 119 employees selected using purposive sampling techniques. Data were collected using workload and work stress scales developed based on relevant theoretical frameworks and tested for validity and reliability. Data analysis using Pearson Product Moment correlation revealed a correlation coefficient of r = 0.614 with a significance value of p = 0.000 (p < 0.05). The coefficient of determination indicates that workload contributes 37.7% to work stress. These results show a significant positive relationship between workload and work stress, meaning that higher workload is associated with higher levels of work stress among employees. Conversely, lower workload tends to be followed by reduced work stress. These findings suggest that workload management plays an important role in maintaining employees’ psychological well-being. Therefore, organizations are encouraged to distribute workloads more proportionally to minimize the risk of work-related stress.